Effect of a CO2 Laser on the Inhibition of Root Surface Caries Adjacent to Restorations of Glass Ionomer Cement or Composite Resin: An In Vitro Study - L. C. Daniel; F. C. Araújo; B. R. Zancopé; F. S. Hanashiro; M. Nobre-dos-Santos; M. N. Youssef; W. C. Souza-Zaroni (The Scientific World Journal)
This study investigated the effect of CO2 laser irradiation on the inhibition of secondary caries on root surfaces adjacent to glass ionomer cement (GIC) or composite resin (CR) restorations. 40 dental blocks were divided into 4 groups: G1 (negative control): cavity preparation + adhesive restoration with CR; G2: (positive control) cavity preparation + GIC restoration; G3: equal to group 1 + CO2 laser with 6 J/cm2; G4: equal to group 2 + CO2 laser. The blocks were submitted to thermal and pH cycling. Dental demineralization around restorations was quantified using microhardness analyses and Light-Induced Fluorescence (QLF). The groups showed no significant differences in mineral loss at depths between 20 μm and 40 μm. At 60 μm, G2 and G3 ≠ G1, but G4 = G1, G2 and G3. At 80 μm, G4 ≠ G1, and at 100 μm, G4 = G2 = G1. At 140 and 220 μm, G2, G3, and G4 = G1. The averages obtained using QFL in groups 1, 2, 3, and 4 were 0.637, 0.162, 0.095, and 0.048, respectively. QLF and microhardness analyses showed that CO2 laser irradiation reduced mineral loss around the CR restorations but that it did not increase the anticariogenic effect of GIC restorations.